An Examination of Interventionist Implementation Fidelity and Content Knowledge as Predictors of Math Intervention Effectiveness. Issue 3 (3rd July 2019) - Nelson, Peter M.; Van Norman, Ethan R.; Parker, David C.; Cormier, Damien C.
Abstract: Data from a large-scale math intervention program were used to evaluate the degree to which implementation fidelity (IF) and interventionist content knowledge were associated with student outcomes. Data were available for 33 interventionists serving 658 students in Grades 4–6 across one school year. A series of multilevel models were fit to the data to evaluate the impact of procedural IF and interventionists' math content knowledge on students' postintervention achievement, controlling for preintervention achievement and intervention dosage. Higher student posttest scores were observed for interventionists with an average fidelity rating of 95% or greater (β = .15); however, no effects on students' math achievement scores were observed for interventionist content knowledge. Adding IF and a measure of interventionist content knowledge to the model explained a statistically significant amount of variance in growth estimates attributable to interventionists (15%). Results highlight the potential importance of ongoing evaluation and remediation of IF in the context of standardized supplemental intervention in math, while also providing some evidence that higher levels of content knowledge may not translate into greater impact in a standard-protocol intervention setting. Results suggest a need for more research examining characteristics of interventionists and aspects of implementation that may account for variance in student outcomes.